Using English as a Medium of Instruction: Challenges and Opportunities of Multilingual Classrooms in Nepal - Paudel, Pitambar (Prithvi Journal of Research and Innovation, 2021)
English as a medium of instruction has great influence in school education in Nepal. It is taken as a pluralistic language which promotes harmony and tolerance, and increases career, opportunities, hope and progress. At the same time, there is a danger of survival for local languages due to the imperialistic role of English. In such a context, this paper has tried to explore the results created due to the extensive use of English as a medium of instruction. To address this objective, the study employs a phenomenological research design under the qualitative approach. The information was collected from eight teachers and eight parents of eight different community schools through interviews and purposively selected two focus group discussions. The collected information from both the tools and sources were coded, triangulated, analyzed, interpreted and presented into three different themes. The results show the use of English as a Medium of Instruction (EMI) in school education as a debatable issue due to the fear of loss of local languages despite its advantages. This implies that the government should make an appropriate language policy and education system to maintain a harmonious and mutual relationship between English and other languages in school education so that children can get opportunities in English language, and become aware of their languages.